Stimulus Taktil Kinestetik terhadap Perubahan Fisiologis Bayi Prematur dengan Perawatan Metode Kanguru - Elvi Febria Marnita; Mayetti Mayetti; Gusti Revilla (Journal of Telenursing (JOTING), 2021)
This study aims to determine the Kinesthetic Tactile Stimulus (STK) effect on premature babies' physiological changes who receive Kangaroo Method Care (PMK). The research design used was a Quasi Experiment with a pretest-posttest two-group design. The sample was 39 preterm babies with simple random sampling. The intervention group of 20 preterm infants was given STK with 15 minutes and the control group was 19 preterm infants without treatment. Physiological measurements of respiration, heart rate, temperature and body weight in both groups were carried out on day 1 and day 5. Statistical analysis used Paired t-test and an Independent t-test. The results showed an effect of STK treatment on decreased breathing, decreased heart rate, increased temperature and increased body weight in the intervention group. The untreated control group showed an effect of increasing temperature and increasing body weight. There was no significant difference in preterm infants' physiological condition in the intervention group and the control group. The conclusion is that STK treatment in the intervention group affects the physiological changes of prematur babies. Keywords: Kangaroo Treatment, Prematur, Kinesthetic Tactile Stimulus